Aerodynamics of wind turbine wakes in flat and complex terrains. (January 2016) - Subramanian, B.; Chokani, N.; Abhari, R.S.
Abstract: The wake evolution measured downstream of multi-megawatt wind turbines located in flat and complex terrains are described here. These high-resolution measurements at full-scale Reynolds number conditions are made with an instrumented drone that is equipped with a suite of sensors and detail the characteristics of the mean flow and turbulent kinetic energy in the evolving wake. Reynolds decomposition yields the nature of turbulent fluctuations in surface layer, and this decomposition is used to detail the turbulence statistics, degree of anisotropy and friction velocity. These measurements are shown to be suited for the further development of three-dimensional wake models that are currently under intensive development. Highlights: Wake evolution detailed at full scale Reynolds number in flat and complex terrains. Near wake characterised by evolution and breakdown of vortices. Far wake characterised by turbulent mixing and re-energisation of flow. Reynolds decomposition yields the nature of turbulent fluctuations in surface layer. Degree of Anisotropy increases in near-wake and decreases in far-wake.